World Literature as a Mode of Critical Reading of Translation - Sutanto, Dian Natalia (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2017)
The study of world literature focuses on how literary work circulates differently worldwide. It is through translation that literary work is circulated and interpreted differently worldwide. The difference in the reception of literary work across places and time is attributed to textual and extra-textual constraints in translation, such as ideology, power, poetics of the time, and institution. To understand how literary work manifests differently abroad than it does at home, critical reading of translation is needed in the study of world literature. The ccritical reading of translation can be done in two ways. The first way is by juxtaposing different translations of the same literary text to explicate the different translation strategies applied by the translators. The ssecond way is by identifying the remainders in the translation to disrupt the transparency of the translation. Both of these ways will reveal cultural differences between target and source culture, and also the influence of iideology, power, poetics and institution to the reception of literary text which varies across places and time. Keywords: world literature, translation, reception of foreign literature, constraints of translation